Perda Manokwari Kota Injil: Makna dan Konsekuensi bagi Gereja-gereja di Indonesia - Binsar Antoni Hutabarat (Societas Dei: Jurnal Agama dan Masyarakat, 2015)
ABSTRACT: This article entitled "Provincial Regulation of Gospel City Manokwari: Significance and Consequences for the Churches in Indonesia" will first explore the presence of Provincial Regulation (Perda or peraturan daerah) of Gospel City Manokwari. The article is based on data collected by the author in a field research in areas related to the initiation of these regulations, and particularly in Manokwari. The author will then analyze this regulation from the standpoint of Christian theology, and further explain the implications of these regulations for the churches in Indonesia. The findings from this study is that Provincial Regulation of Gospel City Manokwari, which is initiated in Manokwari, Papua, is not part of Indonesian Christians strategy in general, and even become a detriment of the testimony of churches in Indonesia.KEY WORDS: Provincial Regulation (Perda or Peraturan Daerah) on religion, Perda on Gospel, the Gospel City Manokwari, state and religion, Christian theology